Tadalafil improves bladder dysfunction and object recognition in rats with pelvic venous congestion. (22nd February 2019) - Nishijima, Saori; Sugaya, Kimio; Kadekawa, Katsumi; Ashitomi, Katsuhiro; Ueda, Tomoyuki; Yamamoto, Hideyuki
Abstract : Objectives: To examine the effects of tadalafil on bladder function and object recognition ability in rats with alterations in urinary frequency and locomotor activity as a result of pelvic venous congestion. Methods: A total of 48 female rats were divided into three groups (sham, pelvic venous congestion and pelvic venous congestion/tadalafil groups). In the pelvic venous congestion and pelvic venous congestion/tadalafil groups, the bilateral common iliac veins and uterine veins were ligated under anesthesia. Rats in the pelvic venous congestion/tadalafil group received a diet containing tadalafil, and the other rats were fed a normal diet. After 4 weeks, rats underwent analysis of voiding behavior, locomotor activity, a novel object recognition test, continuous cystometry, measurement of plasma monoamines, and measurement of plasma and urinary nitric oxide metabolites. Expression of nitric oxide synthase messenger ribonucleic acid in the bladder wall was also assessed, along with histological examination of the bladder. Results: Rats with pelvic venous congestion showed a higher urinary frequency, lower locomotor activity, and lower plasma and urinary nitric oxide levels than sham rats. The bladder wall endothelial nitric oxide synthase messenger ribonucleic acid level was low and object recognition was impaired. Pelvic venous congestion/tadalafil rats showed improvement in locomotor activity, bladder function and object recognition compared with pelvic venous congestion rats, as well as elevation of plasma and urinary nitric oxide, plasma monoamines, and bladder neuronal nitric oxide synthase messenger ribonucleic acid expression. Bladder wall vascularity was greater in pelvic venous congestion/tadalafil rats compared with sham rats. Conclusions: In rats with pelvic venous congestion, tadalafil might improve bladder function and the general condition by increasing blood flow to the bladder and brain, and by increasing dopamine levels.